WOUND CHANGES FOLLOWING DELAYED ADMISSION TO THE BURN CENTER - Yiğit, Ebral; Demir Yiğit, Yasemin (Sanamed, 2023)
Introduction: This retrospective clinical study aimed to investigate patient profiles and wound degree changes, as well as cultural details, resulting from delayed admissions to burn centers following burn trauma.Methods: Patients were categorized into five groups based on the time of hospital admission after the burn trauma: 0 days, 1st day, 2nd day, 3rd day, and 4th day and beyond.Results: During the study period, 1092 patients were admitted to the hospital on the day of their burn trauma. A total of 324 (22.8%) patients—131 (40.4%) women and 193 (59.6%) men—were admitted to the hospital 1 day or more after the trauma. These patients were admitted to the hospital 3.77 (min=1, max=27 ) days after receiving the burn, on average. Of the 324 patients admitted to the hospital after 1 day, 57.9% were rural residents, and 42.1% were urban residents. The most common cause of wound site infection was Staphylococcus aureus, with 20.18%.No statistically significant difference existed between the number of days of delayed hospital admission and the duration of hospitalization.Conclusion: Delays in hospital admission significantly influence changes in burn wound conditions.
Keywords: burn; admission delay; mortality; morbidity